Dual System Curriculum in Chemical Engineering Education - Abdul Halim (Universitas Islam Indonesia, 2022)
Higher education for chemical engineering is required to fulfill several aspects of the required skill and knowledge requested by stakeholders, including professional societies, company partners, accreditation boards, and national standards. Ministry of education of Indonesia under Makarim administration also mandated more liberal practice in Indonesian higher education as jargoned as